Peranan Hukum Acara Mahkamah Konstitusi dalam Menjaga Konstitusionalisme di Indonesia - Alika Hania Auliya; Dedi Mulyadi; Fawazi Rihadatulaisy Mulyadi; Mustika Hidayat; Yasmin Khairunisa; Yudha Adhipratama (Journal of Contemporary Law Studies, 2026)
This study aims to analyze the role of the Constitutional Court’s procedural law in upholding constitutionalism in Indonesia. The method used is normative legal research with a qualitative approach through a literature review, utilizing primary, secondary, and tertiary legal sources. The data was analyzed systematically to understand the authority, functions, and practices of the Constitutional Court within the constitutional system. The results of the study indicate that the Constitutional Court plays a strategic role as a guardian of the constitution through its authority to review laws against the 1945 Constitution, resolve disputes over the authority of state institutions, dissolve political parties, and address disputes regarding election results. The Constitutional Court’s procedural law serves as a crucial guideline to ensure that the review process and decision-making proceed effectively, transparently, and fairly. Additionally, the Constitutional Court plays a role in the impeachment mechanism as a balancing force between legal and political aspects. However, challenges exist in the form of unclear boundaries between legal and political considerations, as well as inconsistencies in the interpretation of legal standing and constitutional harm. This necessitates the strengthening of judicial standards and the consistency of rulings to maintain the institution’s legitimacy and reinforce the supremacy of the constitution and democracy.